1993
DOI: 10.1105/tpc.5.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Interorgan regulation of ethylene biosynthetic genes by pollination.

Abstract: Pollination initiates a syndrome of developmental events that contribute to successful reproduction, including perianth senescence, changes in pigmentation, and ovule differentiation in preparation for impending fertilization. In orchid flowers, initiation of each of these processes in distinct floral organs is strictly and coordinately controlled by pollination, thus providing a unique opportunity to study the signals that coordinate interorgan postpollination development. Because ethylene has been implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
131
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(143 citation statements)
references
References 51 publications
(72 reference statements)
12
131
0
Order By: Relevance
“…A parallel study has demonstrated that the postpollination syndrome of development in orchids, including ovary development, involves coordinated interorgan regulation of expression of ethylene biosynthetic genes (ONeill et al, 1993). Together, these results present the foundation of a molecular model for the regulation of ovary, ovule, and gametophyte development by pollination.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…A parallel study has demonstrated that the postpollination syndrome of development in orchids, including ovary development, involves coordinated interorgan regulation of expression of ethylene biosynthetic genes (ONeill et al, 1993). Together, these results present the foundation of a molecular model for the regulation of ovary, ovule, and gametophyte development by pollination.…”
Section: Introductionmentioning
confidence: 79%
“…Indeed, a model of auxin as the pollination signal was proposed by Burg and Dijkman (1967) whereby auxin from the pollen diffuses through the column where it stimulates ethylene production that in turn triggers senescence of the perianth. We have shown that pollination and auxin induce the expression of genes encoding ACC synthase and ACC oxidase in the gynoecium (ONeill et al, 1993). The pattern of expression is similar for both genes with either of these two stimuli.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Other flowers, such as petunia, gradually senesce over a period of days after flower opening, but this process is accelerated by pollination. In still other flowers perianth senescence is absolutely dependent on pollination and in these cases the external stimuli and endogenous signals that regulate programmed senescence have been examined in detail (O'Neill et al, 1993;O'Neill and Nadeau, 1997;O'Neill, 1997).…”
Section: Flower Senescencementioning
confidence: 99%
“…Programmed cell death in plants: occurrence in development, disease and genetic lesions Programmed cell death regimes in plants are recognized to occur at specific points during development including senescence (Woodson et al, 1992;Smart, 1994), pollination (O'Neill et al, 1993;Zhang and O'Neil, 1993); tracheary element development (Chasan, 1994;Demura and Fukuda, 1994;Fukuda, 1994) and in the formation of aleurone cells in barley and wheat (Wang et al, 1996;Kuo et al, 1996). Analogous to apoptosis in animals, cell death may be triggered in response to pathogens (see reviews by Dangl, 1995;Keen, 1990;Lamb, 1994;Jones and Dangl, 1996;Morel and Dangl, 1997).…”
Section: Introductionmentioning
confidence: 99%